Królowa Saby przed Salomonem – nieznane malowidło Stephana Kesslera w Muzeum Narodowym w Warszawie - Tylicki, Jacek (Sztuka i Kultura, 2021)
Despite being included in the Museum’s collection as early as 1946, the painting has no literature and is being displayed in a corridor of the administrative part of the institution, largely hidden from the public eye. The picture, which can be easily identified by subject, was brought from Silesia and could well originate from the former collection of the Dukes von Hochberg und zu Pless in Hochberg (Książ) castle in that province. This supposition is based on the composition’s resemblance in facial features, architectural detail and overall painterly execution, somewhat coarse, to a set of four pictures, illustrating the Evangelical parable of Prodigal Son, and simultaneously constituting allegories of The Four Seasons, once preserved in that residence. The ensemble, now owned by the National Museum in Wrocław, was signed in 1674 by Stephan Kessler, a painter born in Donauworth in Bavaria and active in Brixen (Bressanone), South Tirol, whose father came from Silesia. The Queen of Sheba, which can be dated to 1660–1670, resembles the Wrocław and many other paintings by Kessler also in large size, in tackling – repeatedly – Biblical and other historical or allegorical themes, and in basing the composition on prints from various periods and milieus, very often made after Rubens, however. In this case, graphic works by Dirck Volckertsz. Coornhert, Matthaus Merian the Elder, and Paulus Pontius seem to have been used. Apart from discussing the main topic, the author reports on two further unpublished pictures by Kessler – a Judith and Holofernes, a partly workshop piece on the Paris art market in 1993, and Moses, Israelites and the Pharaoh’s army drowning in the Red Sea, a good quality work in private possession in Poland.